In silico Docking Analysis for Blocking JUNO‐IZUMO1 Interaction Identifies Two Small Molecules that Block in vitro Fertilization - Stepanenko, Nataliia; Wolk, Omri; Bianchi, Enrica; Wright, Gavin James; Schachter-Safrai, Natali; Makedonski, Kiril; Ouro, Alberto; Ben-Meir, Assaf; Buganim, Yosef; Goldblum, Amiram (Frontiers in Cell and Developmental Biology, 2022)
Combined hormone drugs are the basis for orally administered contraception. However, they are associated with severe side effects that are even more impactful for women in developing countries, where resources are limited. The risk of side effects may be reduced by non-hormonal small molecules which specifically target proteins involved in fertilization. In this paper, we present a virtual docking experiment directed to discover molecules that target the crucial fertilization interactions of JUNO (oocyte)-IZUMO1 (sperm). We docked ~950,000 molecules to two crystal structures of JUNO and ranked them on the basis of energy related criteria. Of the top 32 tested candidates, two molecules (i.e., Z786028994 and Z1290281203) demonstrated fertilization inhibitory effect in both an in vitro fertilization (IVF) assay in mice, and an in vitro penetration of human sperm into hamster oocytes. Despite this clear effect on fertilization, these two molecules did not show JUNO-IZUMO1 interaction blocking activity as assessed by AVidity-based EXtracellular Interaction Screening (AVEXIS). Therefore, further research is required to determine the mechanism of action of these two fertilization inhibitors